HUBUNGAN PENGETAHUAN DAN PERSONAL HIGYENE TERHADAP KEJADIAN KEPUTIHAN PADA IBU HAMIL DI KLINIK BP ANNISA BANYUASIN - Dewi, Ratna; Ernawati, Wahyu; Septiani, Tety (Jurnal Kesehatan dan Pembangunan, 2025)
Based on WHO data, 31.6% of vaginal discharge in pregnant women is caused by candida albicans. Physiological vaginal discharge in pregnant women is normal, so pregnant women must carry out personal hygiene in the genital area during pregnancy so that pathological vaginal discharge does not occur because the impact can cause infertility, pelvic inflammation, premature birth, LBW, KPD, and can cause uterine cancer, pregnancy ectopic, blindness in babies. Research to determine the relationship between knowledge and personal hygiene on the incidence of vaginal discharge in pregnant women at the BP Annisa Banyuasin clinic. Analytical survey research design with a cross sectional approach, the study population was all pregnant women who underwent pregnancy checks at the BP Annisa Banyuasin clinic. The total sampling technique was 85 people. Questionnaire research instrument. Data were analyzed using the Chi Square Test. Results univariate research revealed that 23 (27.1%) pregnant women had good knowledge and 62 (72.9%) had poor knowledge, 33 (38.8%) had good personal hygiene for pregnant women and 52 (61) had poor personal hygiene. 2%), pregnant women who experienced vaginal discharge were 49 (57.6%) and those who did not experience vaginal discharge were 36 (42.4%). The results of the bivariate analysis showed a significant relationship between knowledge and vaginal discharge in pregnant women with a value of P = 0.000 < ? (0.05) and OR = 11.600 and there was a significant relationship between personal hygiene and vaginal discharge in pregnant women with a value P = 0.000 < ? (0 .05) and OR=28.519. Conclusion there is a significant relationship between maternal knowledge and personal hygiene on the incidence of vaginal discharge in pregnant women.